Modelling the acceptance of next generation ICTs: a critical approach - CLAFFEY, ETHEL (My University, 2008)
This PhD research will attempt to model how emerging ICTs may be accepted by the new consumer in today?s social settings. This paper focuses on assessing specific models identified in the literature that could be used to analyse potential consumer behaviour in relation to the adoption or acceptance of emerging ICTs. The consumer decision models and theories developed in the 1960s are still being used to structure research in the field of consumer behaviour. This is despite decision-making today being a more complex phenomenon due to factors such as the digital media revolution and globalisation. Moreover, previous research efforts have concentrated on assessing user acceptance of particular pre-existing technologies rather than investigating the adoption and acceptance process of emerging ICTs. It would seem imperative that marketers embrace the new consumer and gain a deeper insight into the psychological traits and cognitive behavioural antecedents that drive the uptake of emerging Information and Communication Technologies (ICTs). From a theoretical perspective, the study highlights the need for marketing academics to consider more fully the importance of understanding the adoption and acceptance process of next generation ICTs in the current environment. Moreover, the research will seek to make a necessary and timely empirical contribution by examining the current academic research and practice relating to the adoption of ICTs outside the work environment which has been identified as a key area that must me addressed. The research will also seek to make a practical contribution by deriving the relevant implications for marketing managers.
PUBLISHED
Keywords: ICTs; marketing